2012
DOI: 10.1093/molehr/gas059
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic enzyme expression in the human fetal liver and potential role in the endocrinology of pregnancy

Abstract: The human feto-maternal unit produces large amounts of steroid hormones, particularly estrogens, during the second and third trimesters. The fetal adrenal gland and the placenta are considered the principal tissues driving steroid production but the fetal liver is likely to play an essential role in this process. This study was designed to measure transcript expression of proteins involved in steroid synthesis, metabolism, conjugation and signalling in the human fetal liver and to examine sex differences and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 37 publications
4
22
1
Order By: Relevance
“…In our study (O'Shaughnessy et al, 2013), which was not mentioned in the Divakaran et al (2014) publication, we observed no significant difference in hepatic UGT2B15 transcript between male and female fetuses at 11-21 weeks of gestation. This is despite the expression of androgen receptor (AR) transcript and protein in the human fetal liver and the plentiful circulating testosterone in the male human fetus at this time (O'Shaughnessy et al, 2007;.…”
Section: Aspects Of Ugt2b15 In the Humancontrasting
confidence: 48%
See 1 more Smart Citation
“…In our study (O'Shaughnessy et al, 2013), which was not mentioned in the Divakaran et al (2014) publication, we observed no significant difference in hepatic UGT2B15 transcript between male and female fetuses at 11-21 weeks of gestation. This is despite the expression of androgen receptor (AR) transcript and protein in the human fetal liver and the plentiful circulating testosterone in the male human fetus at this time (O'Shaughnessy et al, 2007;.…”
Section: Aspects Of Ugt2b15 In the Humancontrasting
confidence: 48%
“…Taken together, we now know from three well-powered studies that UGBTB15 expression is liver-predominant and climbs steadily from 5 weeks of gestation onwards (Divakaran et al, 2014;Ekstrom et al, 2013;O'Shaughnessy et al, 2013), indicative of an important role in fetal and then adult hepatic function. Furthermore, because of its role in fetal programming, a better understanding of the development of the human liver more generally, and its response to adverse exposure through maternal recreational drugs (including cigarettes and alcohol), is critical.…”
Section: Aspects Of Ugt2b15 In the Humanmentioning
confidence: 88%
“…During the second trimester, the human fetal liver expresses high levels of several steroidogenic enzymes, including aromatase (O’Shaughnessy et al, 2013). At the same time, the expression of steroidogenic enzymes and steroid receptors in the fetal ovary increases (Fowler et al, 2011) (Figure 2).…”
Section: Estrogens Present During Embryonic Developmentmentioning
confidence: 99%
“…O'Shaughnessy et al 23 found higher hepatic SULT2A1 mRNA concentrations in male fetuses of smoking mothers with abortion in the second trimester. Our results did not show any significant difference in fetal SULT2A1 mRNA expression between smoking and non-smoking mothers.…”
Section: Discussionmentioning
confidence: 97%